Singlebeam bathymetry processed data (ODOM Hydrotrac echosounder entire dataset, raw data converted to GIS compatible data formats) of MV MUDLUMP during cruise QB1, Quarantine Bay, United States of America - Alexander Kolker; Dallon Weathers; Swann Christy; Renfro Alisha (PANGAEA, 2025)
This dataset contains bathymetric measurements of Quarantine Bay, located in southeastern Louisiana, USA, on the east side of the lower Mississippi River. Data were collected on 29 September 2022 and 2 November 2022 to investigate the geomorphology of Quarantine Bay, the receiving basin for Neptune Pass—the largest new distributary of the Mississippi River. The bathymetric data also contributed to the development of a sediment budget comparing erosion in Neptune Pass to deposition in Quarantine Bay. Surveys were conducted aboard the University of New Orleans research vessel, R/V Mudlump, using an Odom Hydrotrac single-beam echosounder operating at 200 kHz, mounted on a survey pole. A Trimble R8 real-time kinematic (RTK) GPS unit was positioned 1.86 m directly above the transducer to provide precise vertical and horizontal positioning. To account for vessel motion, a Teledyne DMS-25 motion sensor was affixed to the pole to record heave, pitch, and roll. All data were collected and processed using Hypack hydrographic survey software. The survey area extends from 29.432818°N to 29.384789°N latitude and from -89.522387°W to -89.458752°W longitude.